Nutrient and suspended solid trapping by ceramic induced bubbles - Chan, Kok Min, 1989-; Razali Ismail, supervisor; Fakulti Sains (2012)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2012